Corticosterone alters materno‐fetal glucose partitioning and insulin signalling in pregnant mice. (29th January 2015) - Vaughan, O. R.; Fisher, H. M.; Dionelis, K. N.; Jefferies, E. C.; Higgins, J. S.; Musial, B.; Sferruzzi‐Perri, A. N.; Fowden, A. L.
Key points Glucocorticoids regulate fetal and adult glucose metabolism, in part by influencing the actions of insulin. However, their effects on materno‐fetal glucose partitioning remain largely unknown. In the present study, when pregnant mice were given the natural glucocorticoid, corticosterone, plasma insulin concentrations and liver insulin‐signalling increased but the blood glucose concentration remained normal. However, in the placenta, glucose transport was reduced in association with the lower activity of some insulin signalling proteins, depending on the day of pregnancy and maternal food intake. In both liver and placenta, there was increased expression of the Redd1 (Ddit4) gene when the plasma corticosterone concentration was raised. The results show that maternal glucocorticoids interact with signalling pathways in the placenta to limit materno‐fetal glucose partitioning. Abstract Glucocorticoids affect glucose metabolism in adults and fetuses, although their effects on materno‐fetal glucose partitioning remain unknown. The present study measured maternal hepatic glucose handling and placental glucose transport together with insulin signalling in these tissues in mice drinking corticosterone either from day (D) 11 to D16 or D14 to D19 of pregnancy (term = D21). On the final day of administration, corticosterone‐treated mice were hyperinsulinaemic (P < 0.05) but normoglycaemic compared to untreated controls. In maternal liver, there was no change in glycogen content or glucose 6‐phosphatase activity but increased Slc2a2 glucose transporter expression in corticosterone‐treated mice, on D16 only (P < 0.05). On D19, but not D16, transplacental 3H‐methyl‐d‐glucose clearance was reduced by 33% in corticosterone‐treated dams (P < 0.05). However, when corticosterone‐treated animals were pair‐fed to control intake, aiming to prevent the corticosterone‐induced increase in food consumption, 3H‐methyl‐d‐glucose clearance was similar to the controls. Depending upon gestational age, corticosterone treatment increased phosphorylation of the insulin‐signalling proteins, protein kinase B (Akt) and glycogen synthase‐kinase 3β, in maternal liver (P < 0.05) but not placenta (P > 0.05). Insulin receptor and insulin‐like growth factor type I receptor abundance did not differ with treatment in either tissue. Corticosterone upregulated the stress‐inducible mechanistic target of rapamycin (mTOR) suppressor, Redd1, in liver (D16 and D19) and placenta (D19), in ad libitum fed animals (P < 0.05). Concomitantly, hepatic protein content and placental weight were reduced on D19 (P < 0.05), in association with altered abundance and/or phosphorylation of signalling proteins downstream of mTOR. Taken together, the data indicate that maternal glucocorticoid excess reduces fetal growth partially by altering placental glucose transport and mTOR signalling.